Gallstone ileus: A case report - Batubara, Immanuel Van Donn; Lesmana, Tomy (Edelweiss Applied Science and Technology, 2025)
Gallstone ileus is a condition where there is a mechanical obstruction of the intestinal lumen caused by gallstones and is a rare complication of cholelithiasis. The prevalence of gallstone ileus is approximately 5% of all patients with intestinal obstruction. We present a female patient with intestinal obstruction caused by gallstone ileus who was treated with laparotomy enterolithotomy for gallstone evacuation. A 64-year-old female patient came to the Emergency Department of Dr. Soetomo Surabaya Hospital with complaints of nausea and vomiting after eating and drinking. The patient reported not being able to defecate for 5 days, followed by an inability to pass gas, with the last instance of flatulence occurring 1 day before entering the hospital. The patient was planned for laparotomy enterolithotomy to evacuate gallstones. The pathophysiology of gallstone ileus involves the obstruction of the intestines due to the impaction of one or more gallstones. This condition is commonly preceded by the initial symptoms of acute cholecystitis. The primary objective in managing gallstone ileus is to alleviate the intestinal obstruction by extracting the gallstone from the intestinal lumen. The author believes that in this case report, enterolithotomy was performed as it has a lower mortality and morbidity rate compared to a single-stage procedure.